Immunopharmacology of the Main Herbal Supplements: A Review - P. Amico, Angelo; Terlizzi, Annamaria; Damiani, Sabino; Ranieri, Maurizio; Megna, Marisa; Fiore, Pietro (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2013)
It is debated whether the use of herbal supplements in endurance sports, in order to have a better performance, is correct or not, from the perspective of both as safety and as effectiveness. In this review we try to find out if the most common herbal supplements (Echinacea, Rhodiola, Ginseng) are effective in the improvement of performance or in the modulation of the immune system. According to the results of our review, the prevalent effect is adaptogenic rather than ergogenic, with a better tolerance of the exercise induced stress, related to enhancement of the whole immune system and decrease of the oxidative damage.
Keywords: echinacea